Distance, flow and PCR inhibition: eDNA dynamics in two headwater streams. (13th June 2014) - Jane, Stephen F.; Wilcox, Taylor M.; McKelvey, Kevin S.; Young, Michael K.; Schwartz, Michael K.; Lowe, Winsor H.; Letcher, Benjamin H.; Whiteley, Andrew R.
Abstract Environmental DNA (eDNA) detection has emerged as a powerful tool for monitoring aquatic organisms, but much remains unknown about the dynamics of aquatic eDNA over a range of environmental conditions. DNA concentrations in streams and rivers will depend not only on the equilibrium between DNA entering the water and DNA leaving the system through degradation, but also on downstream transport. To improve understanding of the dynamics of eDNA concentration in lotic systems, we introduced caged trout into two fishless headwater streams and took eDNA samples at evenly spaced downstream intervals. This was repeated 18 times from mid‐summer through autumn, over flows ranging from approximately 1–96 L/s. We used quantitative PCR to relate DNA copy number to distance from source. We found that regardless of flow, there were detectable levels of DNA at 239.5 m. The main effect of flow on eDNA counts was in opposite directions in the two streams. At the lowest flows, eDNA counts were highest close to the source and quickly trailed off over distance. At the highest flows, DNA counts were relatively low both near and far from the source. Biomass was positively related to eDNA copy number in both streams. A combination of cell settling, turbulence and dilution effects is probably responsible for our observations. Additionally, during high leaf deposition periods, the presence of inhibitors resulted in no amplification for high copy number samples in the absence of an inhibition‐releasing strategy, demonstrating the necessity to carefully consider inhibition in eDNA analysis.